Quantitative proteomic analysis of mitochondria from human ovarian cancer cells and their paclitaxel‐resistant sublines. Issue 8 (24th July 2015) - Chen, Ming; Huang, Hong; He, Haojie; Ying, Wantao; Liu, Xin; Dai, Zhiqin; Yin, Jie; Mao, Ning; Qian, Xiaohong; Pan, Lingya
<x xml:space="preserve">Abstract</x> Paclitaxel resistance is a major obstacle for the treatment of ovarian cancer. The chemoresistance mechanisms are partly related to the mitochondria. Identification of the relevant proteins in mitochondria will help in clarifying the possible mechanisms and in selecting effective chemotherapy for patients with paclitaxel resistance. In the present study, mitochondria from two paclitaxel‐sensitive human ovarian cancer cell lines (SKOV3 and A2780) and their corresponding resistant cell lines (SKOV3‐TR and A2780‐TR) were isolated. Guanidine‐modified acetyl‐stable isotope labeling and liquid chromatography‐hybrid linear ion trap Fourier‐transform ion cyclotron resonance mass spectrometry (LC‐FTICR MS) were performed to find the expressed differential proteins. Comparative proteomic analysis revealed eight differentially expressed proteins in the ovarian cancer cells and their paclitaxel‐resistant sublines. Among them, mimitin and 14‐3‐3 ζ/δ were selected for further research. The effects of mimitin and 14‐3‐3 ζ/δ were explored using specific siRNA interference in ovarian cancer cell lines and immunohistochemistry in human tissue specimens. The downregulation of mimitin and 14‐3‐3 ζ/δ using specific siRNA in paclitaxel‐resistant ovarian cancer cells led to an increase in the resistance index to paclitaxel. Multivariate analyses demonstrated that lower expression levels of the mimitin and 14‐3‐3 ζ/δ proteins were positively associated with shorter progression‐free survival (PFS) and overall survival (OS) in patients with primary ovarian cancer (mimitin: PFS: P = 0.041, OS: P = 0.003; 14‐3‐3 ζ/δ: PFS: P = 0.031, OS: P = 0.011). Mimitin and 14‐3‐3 protein ζ/δ are potential markers of paclitaxel resistance and prognostic factors in ovarian cancer.